Analisis Praktik Menyusui Dan MPASI Pada Ibu Di Lingkungan Pangkabinanga Kabupaten Gowa - Idris, Fairus Prihatin; Sididi, Mansur; Sriwahyuni, Riska; Arini, Sri; Musdalivah, Musdalivah; Janna, Miftahul; Yakub, Rihhadatul Adzroo (Universitas Wiralodra, 2025)
This study aims to identify and analyze the practices of breastfeeding and child care among mothers living in the Pangkabinanga neighborhood, Pangkabinanga Village, Pallangga District, Gowa Regency, in 2024. This research employs a quantitative approach with a descriptive method. The variables studied include the implementation of Early Initiation of Breastfeeding (IMD), the provision of breast milk including colostrum, and the provision of food or drinks before breastfeeding. The population in this study consists of all mothers with infants in the area, with a sample size of 28 respondents selected through total sampling. Data was collected through structured interviews using questionnaires. The results of the study show that the majority of mothers have practiced IMD (85.7%) and have breastfed their children (92.9%). As many as 85.7% of mothers provided colostrum, and 92.9% of children were not given food or drinks other than breast milk. However, some children stopped breastfeeding after 6 months (64.3%), while 14.3% are still being breastfed. The most common first food given other than breast milk is rice porridge (42.9%) and fruit (39.2%). These findings indicate that while breastfeeding practices are generally good, further interventions are needed to increase exclusive breastfeeding rates and prevent the provision of food or drinks other than breast milk before the appropriate time. This study is expected to provide input for health policies aimed at raising awareness about the importance of exclusive breastfeeding in the community.